Forecast of the hailstorm event on March 21, 2021 in the Northwest region of Vietnam using numerical model - Minh Truong, Nguyen; Manh Duy, Doan (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1SDO - 10.25073/2588-1094/vnuees.5388, 2025)
This study uses the WRF model to forecast the hailstorm event of March 21, 2021 in the Northwestern provinces of Vietnam, based on three hail size prediction indices: the Maximum Estimated Size of Hail from simulated reflectivity (MESH_WRF), the Thompson algorithm (Dmax), and the WRF-Hailcast model (HC). Using two microphysics schemes, Milbrandt–Yau (MY2) and Morrison (MOR), the model was able to forecast the development of the hail-producing convective system, in terms of both location and intensity. When evaluated against radar-derived MESH data, the Dmax index from MY2 showed the highest skill in predicting hail occurrence area. Both MESH_WRF products overforecasted the hail area, while HC had almost no predictive capability for this event. Microphysical analysis of the largest convective cell revealed that the hail phase in MY2 had a lower distribution and larger mean size at low levels compared to the graupel phase in MOR. As a result, the MESH_WRF and Dmax products from MY2 provided better forecasts than those from MOR.   Keywords: Hail, MESH, WRF, Microphysics